Poetry, Pictures, and Popular Publishing : The Illustrated Gift Book and Victorian Visual Culture, 1855-1875 - Janzen Kooistra, Lorraine, 1953- (Book collections on Project MUSE., 2011)
"Poetry, Picture, and Popular Publishing demonstrates the cultural centrality of a neglected artifact: the Victorian Illustrated gift book. Kooistra reveals how the gift book's visual/verbal form mediated "high" and popular art as well as book and periodical publication. A composite text produced by many makers, the poetic gift book was designed for domestic space and a female audience. With rigorous attention to the gift book's aesthetic and ideological features, Kooistra analyzes the contributions of poets, artists, engravers, publishers, and readers and shows how its material form moved poetry into popular culture. Drawing on archival and periodical research, she offers new readings of Eliza Cook, Adelaide Procter, and Jean Ingelow and shows the transatlantic reach of their verses. Boldly resituating Tennyson's works within the gift-book economy he dominated, Kooistra demonstrates how the conditions of corporate authorship shaped the production and reception of the laureate's verses at the peak of his popularity"--